Astroparticle physics as a telescope for solar interior, galactic and extragalactic structures - D'Alessi, Loris; Bartolino, Roberto; Carbone, Vincenzo (My University, 2013)
Astroparticle physics provide a fundamental tool to investigate the astrophysical structures at different scales. In this thesis the results are presented of three years of research focused on time variations on solar neutrino flux, galactic cosmic rays and fine-structure constant as observed from quasar spectra. These topics are nowadays crucial to investigate structures which otherwise result difficult to probe. In particular time variations in solar neutrinos can give a real time description of the dynamics which take place in the inner regions of the Sun, while the study of galactic cosmic rays through the observation of muons produced by the interaction of the formers with the atmosphere, may give us precious informations on the interaction between TeV particles and heliospheric magnetic fields. Finally the recent observations of variations in the fine-structure constant value from the analysis of quasar absorption spectra, offer new possibilities to probe physical laws at cosmological scales. The thesis is structured as follows. In Chapter One are discussed quasi-biennial oscillations observed on solar neutrino flux and a phenomenological model is proposed to interpret the observed time variations. In the scenario described by the model, the interaction between solar neutrinos and solar matter mediated by magnetogravity modes, is modulated by a background magnetic field varying in time on quasi-biennial time scales. In Chapter Two the 11-yr component recently observed in cosmic muon data from Gran Sasso experiments of MACRO, LVD and Borexino has been reconstructed through the EMD analysis technique. In Chapter Three the data of fine-structure constant variations as observed in the quasar absorption spectra have been analyzed to search for temporal coherent structures. The thesis is completed by the description in appendix of a new algorithm based on Monte Carlo methods to assign a confidence interval to the IMFs extracted with the EMD analysis, and the application of this method to study the proton and neutrino distributions used in the OPERA experiment for the neutrino velocity measurement. Another appendix is dedicated to detailed description of the effects induced on the magnetogravity spectrum by a background magnetic field with a low-pass bandwidth, thus generalizing the theory of magneto-gravity modes in presence of a time-dependent background magnetic field.
Scuola di Dottorato Scienza e Tecnica "Bernardino Telesio", Fisica dei Sistemi Complessi, Ciclo XXVI, a.a. 2013
Keywords: Astronomia; Astrofisica; Costanti fisiche; Neutrini; Raggi cosmici